Biochar soil amendment as carbon farming practice in a Mediterranean environment - Nogués, I.; Mazzurco Miritana, V.; Passatore, L.; Zacchini, M.; Peruzzi, E.; Carloni, S.; Pietrini, F.; Marabottini, R.; Chiti, T.; Massaccesi, L.; Marinari, S. (Geoderma Regional, 2023)
Carbon Farming is a new approach for land management that allows the sequestration of carbon in the soil and plants, mitigating the emission of greenhouse gases. It includes a set of eco-friendly strategies. Among them, increasing of carbon content through the application of biochar seems to be particularly promising for the Mediterranean area, where erosion and loss of organic matter is a relevant problem for agricultural production. Although soil amendment with biochar has received significant and increasing attention during the last decade, few studies have been focused on the Mediterranean basin. In this review, state of the art use of biochar as carbon farming practice in the Mediterranean region from the legislative, policy and scientific point of view has been discussed. Throughout the review, a description of the main results obtained from 36 studies carried out at 23 different field locations, with regard to carbon dynamics, soil water holding capacity (WHC) and crop yield has been reported. As a concluding remark, it is observed that biochar has good potential to store carbon in Mediterranean soils; it has a good proportion of recalcitrant carbon and can effectively improve soil water content under limited water conditions such as during drought and summer. However, long-term field studies on various Mediterranean soils should be performed in order to reach valid conclusions on the effects of biochar on the plant-soil system in the Mediterranean basin. In this context, it is essential to report a set of basic parameters to link the main characteristics of biochar, and its effects on soil and plant productivity. •Biochar has good potentialities to store carbon in Mediterranean soils.•Biochar use can help to the adaptation of Mediterranean cropping systems to climate change.•Biochar can effectively improve soil water content under limited water condition.•It would be desirable to have a higher number of field studies with a relevant dataset of basic parameters.•The EC is designing policies that will translate carbon farming mitigation potential into real actions.